My life a Fragment : An Autobiographical Sketch of Maulana Mohamed Ali - Ali, Mohamed 1878-1931; Edited by Iqbal, Afzal (Kashmiri Bazar, Lahore Sh. Muhammad Ashraf, 1966)
By an Indian Muslim nationalist and politician
Keywords: Ali, Mohamed, 1878-1931 -- Nationalists -- India -- Biography -- Politicians -- India -- Biography